Evaluasi Pelaksanaan Rencana Kerja DPRD Kota Serang Tahun 2019 - Desi Marlina; Ismanto; Leo Agustino (Epistemik Press, 2022)
The Work Plan of the Regional House of Representatives (DPRD) does not only contain planning for program activities but is also a manifestation of the implementation functions, that are the function of formatting the regional regulations, budget function, and monitoring function. However, in 2019 there were presidential and legislative elections held simultaneously for the first time in Indonesia. Logically, this will have an impact for the leaders and members of the DPRD who are the region political actors in carrying out their duties and functions as specified in the work plan. Moreover, in that year there were two periods of DPRD membership, the 2014-2019 term and the 2019-2024 term. This research aims to evaluate the implementation work plan of the Serang City Regional House of Representatives in 2019 which is focused on the implementation of the program activities and functions. Researchers use evaluative research design with a qualitative descriptive approach which was developed based on the evaluation criteria presented by William N. Dunn. The findings of this study explain that the work plan activity program is carried out according to the schedule set by the Badan Musyawarah considering the election stages of the KPU and adjustments to the political agenda of the leaders and members of the DPRD. Meanwhile, in the implementation of DPRD functions in 2019, the weakest function is the monitoring function. It is because the monitoring that has been evaluated so far is a field visit activity or often also called an inspection. Whereas monitoring can also take the form of work meetings, meetings to discuss regional regulations, or other activities that actually can also be in the form of monitoring the performance of local governments.